1973
DOI: 10.1044/jshr.1603.397
|View full text |Cite
|
Sign up to set email alerts
|

Labial and Mandibular Dynamics during the Production of Bilabial Consonants: Preliminary Observations

Abstract: Simultaneous recordings of upper lip, lower lip, and jaw movements concomitant with intramuscular electromyography were obtained from five subjects during the production of VCV tokens where V = /i/, /ε/, and /æ/ and C = /p/, /b/, and /m/. The temporal sequencing of muscle activity from major elevators and depressors of the lips and jaw was determined and incorporated into a preliminary description of the motor control of the bilabial gesture. Magnitudes of articulator displacement and velocity and electromyogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
2
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(60 citation statements)
references
References 0 publications
6
51
2
1
Order By: Relevance
“…Similar to locomotion (Grillner and Zangger, 1975), muscle onsets were found to be highly related, although there was no consistent sequence of onsets across subjects. Previous EMG studies of jaw and lip muscles during speech have also reported inconsistent ordering of muscle onsets across subjects (Sussman et al, 1973;Folkins, 1981).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to locomotion (Grillner and Zangger, 1975), muscle onsets were found to be highly related, although there was no consistent sequence of onsets across subjects. Previous EMG studies of jaw and lip muscles during speech have also reported inconsistent ordering of muscle onsets across subjects (Sussman et al, 1973;Folkins, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…For all subjects muscle activity was sampled from 2 upper lip depressor muscles-orbicularis oris superior (00s) and depressor anguli oris (DAO)-and 2 lower lip elevators-orbicularis oris inferior (001) and mentalis (MTL). Electrode placements were based on anatomical landmarks from cadaveric studies (Kennedy and Abbs, 1979;Kahane and Folkins, 1984) and functional verification (Sussman et al, 1973). While anatomical localization of specific perioral muscles is problematic due to interdigitation of muscle fibers (Blair and Smith, 1986), verification procedures (e.g., the onset and offset of muscles consistent with their actions based on known orientation of muscle fibers, and the cessation of activity during antagonistic actions; see Smith et al, 1985) suggested that the muscles sampled were providing functionally specific electromyographic (EMG) information.…”
Section: Methodsmentioning
confidence: 99%
“…Much of this context dependence emerges lawfully from the use of task dynamics. An example of this kind of context dependence in lip closure gestures can be seen in the fact that the three independent articulators that can contribute to closing the lips (upper lip, lower lip, and jaw) do so to different extents as a function of the vowel environment in which the lip closure is produced (Macchi, 1988;Sussman, MacNeilage, & Hanson, 1973). The value of lip aperture achieved, however, remains relatively invariant no matter what the vowel context.…”
Section: Gesturesmentioning
confidence: 99%
“…Unfortunately, they did not manipulate higher formants, which also vary in frequency at voicing offset as a function of consonant voicing (Nittrouer, Estee, Lowenstein, and Smith, submitted). Furthermore, the changing (i.e., dynamic) nature of formant transitions is generally considered to be critical to speech recognition for both adults and children (e.g., Browman and Goldstein, 1990;Miranda and Strange, 1989;Nittrouer, Manning, and Meyer, 1993;Strange, 1989;Sussman, MacNeilage, and Hanson, 1973), owing in part to demonstrations that listeners can understand signals in which sinusoids are substituted for center formant frequencies (e.g., Remez, Rubin, Pisoni, and Carrell, 1981). In these "sinewave" signals, many acoustic properties traditionally associated with phonetic perception are missing.…”
Section: Introductionmentioning
confidence: 99%